Negligible effects of blood sampling on reproductive performance and return rates of Tree Swallows. Issue 1 (28th December 2018) - Orzechowski, Sophia C. M.; Shipley, J. Ryan; Pegan, Teresa M.; Winkler, David W.
Abstract: Blood sampling is a frequently used method of collecting genetic and physiological data in natural populations, and understanding the possible impact of blood sampling on individuals and populations is important, both for the welfare of study organisms and to avoid introducing bias into analyses using bled individuals. Most studies of birds have revealed minimal negative effects of blood sampling. However, Brown and Brown (2009. Auk 126: 853–861) found that blood sampling reduced return rates of Cliff Swallows ( Petrochelidon pyrrhonota ), suggesting that these results are not always generalizable and that swallows (Hirundinidae) may be particularly sensitive to blood sampling. We examined the possible effects of blood sampling on the reproductive performance of female Tree Swallows ( Tachycineta bicolor ) and the return rates of both females and offspring in a population in New York state. To reduce the chances of Type II error, we tested 15 possible effects of blood sampling on reproductive performance and return rates using generalized linear mixed models. Overall, our results suggest that blood sampling had few negative effects on within‐year reproductive success or survival of adult females. The one exception was that bleeding nestlings had a negative effect on the number of young that fledged in broods of five or six nestlings. Bleeding did not negatively impact return rates of females or nestlings in our Tree Swallow population. Our results support those of other studies suggesting that blood sampling has few negative effects on within‐year reproductive success or survival of adult females, and reiterate the importance of systematically testing for possible effects with datasets compiled over multiple years because such effects may be impossible to detect via direct monitoring during a single breeding season.